Mangrove Conservation in Kampot Province, Cambodia - Channa Rein; Serey Mardy (MultiTech Publisher, 2023)
Mangrove is a plant that is always seen in tropical and subtropical coastal areas, along coastal lagoons, the margins of estuaries, and deltas as well. Cambodia has a long coastline of 435 kilometers across four provinces: Koh Kong, Preah Sihanoukville, Kep, and Kampot, which have rich natural resources such as mangroves. Because of humans and nature, 36,810 ha of mangrove forest were damaged between 1989 and 2017. This review aims: (1) to find out the reason for mangroves to be managed; (2) to define the problem of degradation of mangroves; and (3) to find out the method for restoring and conserving mangroves in Kampot Province. This review uses a qualitative approach to collect data from another document of the journal that was published; the website, the book, and the report combine it on the desk and analyze it by using secondary data as a qualitative and quantitative method. In this review, we found the mangrove forest has provided many benefits, both human, economic, and environmental. It is a renewable resource that must be managed and conserved in a sustainable way. The forest of mangroves has equity concerns about achieving the optimum forest products and services to fulfill the needs of recent generations without destroying them. Conserving mangrove forests is our role, together with that of future generations.